PERAN PENDIDIKAN SEKS DALAM UPAYA PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA: PERSPEKTIF HUKUM ISLAM - Diana Sari; Mawarda Mawarda (Syariah: Jurnal Hukum Keluarga Islam, 2025)
Sex education plays a very important role in tackling the increasing incidence of sexual violence in Indonesia. Preventive and curative measures can be a solution in reducing the incidence of sexual violence in the household. This study aims to analyze the role of sex education in preventing sexual violence in the household. The legal research method used is a literature study that looks at previous cases, integrating a socio-juridical and normative legal approach. This approach is an effort to identify indicators of problems related to the laws and regulations that apply in society. By providing the community with an understanding of sex education, gender equality, sexual rights, and consent. Sex education involves the cooperation of all parties, including legal institutions, families, and the community, in an effort to provide protection, education, and healthy communication to prevent domestic violence